Bottom‐Up Molecular Tunneling Junctions Formed by Self‐Assembly. Issue 5 (9th May 2014) - Zhang, Yanxi; Zhao, Zhiyuan; Fracasso, Davide; Chiechi, Ryan C.
Abstract This Minireview focuses on bottom‐up molecular tunneling junctions – a fundamental component of molecular electronics – that are formed by self‐assembly. These junctions are part of devices that, in part, fabricate themselves, and therefore, are particularly dependent on the chemistry of the molecules selected. The discussion covers the history of these junctions as well as recent advances. It is broken into the broad categories of conformal and rigid contacts, which place different constraints on the molecules used to form the junctions. The intention of this Minireview is to give an overview of research efforts in molecular electronics that is targeted at chemists, whose efforts are playing an increasingly important role in molecular electronics.